Pharmacy students’ attitudes to provide rational pharmaceutical care: A multi-institutional study in Jordan - Nusair, Mohammad; Alhamad, Hamza; Mukattash, Tareq; Al-sheyyab, Raghad; Alazzam, Sayer (Jordan Journal of Pharmaceutical Sciences, 2021)
This study aims to assess the Jordanian pharmacy students' attitudes and perceptions toward providing rational pharmaceutical care. The study was conducted by administering an anonymous online survey (Standard Pharmaceutical Care Attitude Survey; PCAS) to pharmacy students at five public universities in Jordan. Descriptive statistics were used to describe participants response on the questionnaire items and one-way ANOVA were used for inferential statistics. A total of 884 responses met the eligibility criteria. The majority of participants (n=614, 69.5%) reported that they have been introduced to the pharmaceutical care concept in their program. The majority of participants reported positive attitudes toward the professional duty and benefit of pharmaceutical, more negatives attitudes were reported toward the return on effort. Participants who had a clerkship experience had significantly more positive attitudes toward six items of the PCAS. In conclusion, pharmacy students in Jordan have positive attitudes toward providing rational pharmaceutical care. The majority, however, perceived pharmaceutical care to be time-consuming and not worth the additional workload that it places on pharmacists. This study highlights opportunities to achieve more positive attitudes by mandating pharmaceutical care courses in pharmacy schools in Jordan and exposing students to real-world scenarios.